استخدام التحليل بالمنطق الضبابي والذكاء الاصطناعي كإحدى الطرق الرياضية المساعدة في اتخاذ القرار بالمؤسسات الاقتصادية: دراسة بيبليومترية: Using Fuzzy Logic Analysis and Artificial Intelligence as a Mathematical Aid to Decision Making in Business Organizations: A Bibliometric Study - ادريسي مختار; عبرو جبلي; صوار يوسف (Journal of North African Economies, 2025)
This article aims to highlight the importance of fuzzy logic analysis and artificial intelligence (AI)as modern mathematical tools that contribute to decision-making in economic institutions. Fuzzy logic analysis is considered one of the most important mathematical tools for dealing with the ambiguity and uncertainty associated with the complexity of an institution's economic environment. Bibliometric analysis was applied to a sample of 61 articles extracted from the Scopus database due to its ease of data access. The data collected were processed using R statistical software. The results of the study show that research trends in the use of fuzzy logic and artificial intelligence in the decision-making processes of economic institutions worldwide are still limited but increasing. The study also shows that research into the use of fuzzy logic and artificial intelligence in the decision-making processes of economic organizations worldwide is still limited but steadily increasing. This underlines the importance of using fuzzy logic and artificial intelligence as mathematical tools to improve decision-making processes in business organizations.